I Wan’na Be Like You-ou-ou: Tracing the Deconstruction of Anthropocentrism in Disney’s The Jungle Book (1967) - Uys, Hugo (The Stellenbosch Socratic Journal, 2023)
Contemporary society is undeniably marred by the routine violence which it exacts upon animals. For post-structuralist thinkers, this violence begins with the anthropocentrism of human language. This paper thus follows the post-structuralist work of Jacques Derrida, specifically his strategy of deconstruction, in order to disrupt the anthropogenic violence continually inflicted upon animal beings. In so doing, this paper aims to contribute to the ongoing destabilisation of the anthropocentric human(animal) hierarchy by tracing the deconstruction of anthropocentrism in Disney’s The Jungle Book (1967). Accordingly, I draw on Derrida’s strategy of deconstruction to show how the ostensibly stable human(animal) hierarchy is underwritten by anthropocentrism which is always already contingently established and prone to reversal – and hence, open to its own displacement as a matter of ethico-political urgency. Ultimately, it is shown that The Jungle Book, upon its deconstruction, does not merely reconfigure the human-animal relationship, but renders the very term ‘animal’ nonsensical.